A One Stone Three Birds Paradigm of Photon‐Driven Pyroptosis Dye for Amplifying Tumor Immunotherapy - Shuang Zeng; Chen Chen; Dan Yu; Maojun Jiang; Xin Li; Xiaosheng Liu; Zhihan Guo; Yifu Hao; Danhong Zhou; Heejeong Kim; Heemin Kang; Jingyun Wang; et al. (Advanced Science)
Abstract Activating the pyroptosis pathway of tumor cells by photodynamic therapy (PDT) for immunogenic cell death (ICD) is considered a valid strategy in pursuit of antitumor immunotherapy, but it remains a huge challenge due to the lack of reliable design guidelines. Moreover, it is often overlooked that conventional PDT can exacerbate the development of tumor immunosuppressive microenvironment, which is apparently unfavorable to clinical immunotherapy. The endoplasmic reticulum's (ER) pivotal role in cellular homeostasis and its emerging link to pyroptosis have galvanized interest in ER‐centric imaging and therapeutics. Herein, using the targeted group‐assisted strategy (TAGS), an intriguing cyclooxygenase‐2‐targeted photodynamic conjugate, Indo‐Cy, strategically created, which exploits the enzyme's overabundance in the tumoral ER, especially under proinflammatory hypoxic conditions. This conjugate, with its highly precise ER imaging, embodies a trifunctional strategy: i) innovating an electron transfer mechanism, converting the hemicyanine moiety into an oxygen‐independent type I photosensitizer, thereby navigating around the hypoxia constraints of traditional PDT; ii) executing precise ER‐targeted PDT, amplifying caspase‐1/GSDMD‐mediated pyroptosis for ICD; 3) attenuating immunosuppressive pathways by inhibiting cyclooxygenase‐2 downstream factors, including HIF‐1α, PGE2, and VEGF. Indo‐Cy's multimodal approach potently induces in vivo tumor pyroptosis and bolsters antitumor immunity, underscoring cyclooxygenase‐2‐targeted dyes' potential as a versatile oncotherapeutics.